DIRECT DESIGN SOLUTION FOR CASSEGRAIN SHIELDS - MALACARA HERNANDEZ, D; CORNEJO, AURELIO (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1965)
A direct algebraic design of Cassegrain light shields is proposed, using only the assumption that the mirror surfaces are flat.
BOL OBS TONAN TACUB
Keywords: DIRECT, DESIGN, SOLUTION, CASSEGRAIN SHIELDS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS